Application of Fuzzy Linear Programming to Optimize the Amount of Chicken Production Using Tsukamoto Method (Case Study: Ayam Geprek XYZ) - Erwin; Simbolon, Angelika; Batubara, Agnes; Br Ginting, Julhanna (Talenta Publisher, 2023)
Fuzzy linear Programming is the development of a linear program model to find and determine the optimal value containing fuzzy values. To optimize the amount of raw chicken production, this research uses the Tsukamoto method and Fuzzy Linear Programming (FLP). This case study is focused on Ayam Geprek Campus Habibi. Market demand, raw material availability, and production capacity are some of the factors that affect raw chicken production. The FLP method with Tsukamoto approach is used to handle diversity and uncertainty in decision making about chicken production. A case study was conducted to show that this technique is effective in improving production efficiency and resulting in more optimized raw chicken production management decisions. The results of this study are expected to increase our understanding of the application of FLP with Tsukamoto method in the food industry, particularly on how to optimize raw chicken production.